2016
DOI: 10.1159/000448000
|View full text |Cite|
|
Sign up to set email alerts
|

Prospective, Randomized Study on the Efficacy and Safety of Local UV-Free Blue Light Treatment of Eczema

Abstract: Background: Blue light was shown to reduce the activation of T cells and modulate cytokine release in vitro. Therefore, we investigated the efficacy of blue light in the treatment of eczema. Methods: A sample of 21 patients with mild to moderate eczema were locally treated with blue LED light (light-emitting diode, emission maximum: 453 nm). They received light treatment 3 times per week for 4 weeks. A contralateral control lesion remained untreated. Results: A total of 20 patients completed the trial with a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 14 publications
0
45
0
4
Order By: Relevance
“…After 5 years of observation, the prevalence of psoriasis, lichen, dyschromia, hair/hair follicle disorders, skin cancer, and total cancer was not increased in the phototherapy group. Other studies also indicated that blue light was safe -clinically [3][4][5], histologically [4], and in vitro [12,13]. Thus far, the only reported adverse effect was temporary hyper-pigmentation of the skin treatment area [14].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…After 5 years of observation, the prevalence of psoriasis, lichen, dyschromia, hair/hair follicle disorders, skin cancer, and total cancer was not increased in the phototherapy group. Other studies also indicated that blue light was safe -clinically [3][4][5], histologically [4], and in vitro [12,13]. Thus far, the only reported adverse effect was temporary hyper-pigmentation of the skin treatment area [14].…”
Section: Discussionmentioning
confidence: 97%
“…UV-free blue light has been reported to treat allergic skin disease [3][4][5]; however, it is used less often than UV light in the clinical setting. Moreover, the treatment effect and small sample size (10-36 subjects) of previous studies * Adjusted for confounding factors: sex, socioeconomic status, urbanization, special healthcare needs, congenital skin disease, neonatal infection, preterm status, low birth weight, high birth weight, and other birth or maternal conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional evidence in this respect came from in vitro studies using HaCaT cells, where gene expression analysis showed downregulated pathways implicated in inflammatory responses, and using dendritic cells, where a reduced ability to release pro‐inflammatory cytokines was shown . At the clinical level, the recently reported positive impact of blue light on alleviating symptoms of psoriasis vulgaris (PV) and atopic dermatitis (AD), chronic inflammatory skin diseases characterized by hyperproliferation and inflammatory infiltrates, holds promise for its therapeutic potential …”
Section: Introductionmentioning
confidence: 99%
“…Setting the focus on the latter, the primary objective of this study was to investigate the impact of UV‐free blue light at 453 nm on the recovery of the skin barrier and on the cutaneous inflammatory response elicited by acute perturbation of the skin of healthy human volunteers. While blue light has already proven effective in clinical studies on diseased skin, data on its biological effects on perturbed but otherwise healthy skin are scarce. Skin reactions were evaluated up to 72 hours after stimulation using several noninvasive biophysical measurements.…”
Section: Introductionmentioning
confidence: 99%